Strategies for Innovation and Interdisciplinary Translational Research: Research and Career Benefits and Barriers. (1st February 2009) - Benedyk, Mark; Berglund, Lars; Facciotti, Marc; Mobley, William; Zucker, Deborah
Abstract : Following is a portion of the proceedings of the panel and audience discussion from the AFMR-Translational Medical Research Development Workshop at EB08.